(untitled) (Journal of Computational Mathematics, 1989)
The spectral function μ(t)=_j=1^∞ e^-itλ^12 _j where {λ_j}^∞_j=1 are the eigenvalues of the three-dimensional Laplacian is studied for a variety of domains, where - ∞＜t＜∞ and i=-1. The dependence of μ(t) on the connectivity of a domain and the impedance boundary condition (Robbin conditions) are analyzed. Particular attention is given to the spherical shell together with Robbin boundary conditions on its surface.